Pengaruh Promotion Mix terhadap Keputusan Pemilihan Merek Oli Mobil Pada Pantai Gading Motor Palangkaraya - Miftah Farid; Saladin Ghalib; Setio Utomo (JURNAL BISNIS DAN PEMBANGUNAN, 2014)
The aim of this study is to determine andnalyze the promotion mix (promotion mix) which is a tool of marketing mix that includes all activities of the company to communicate and to promote their products to the target market. As applied by Pantai Gading Motor Palangkaraya in promoting the brand of car oil that they sell to their consumers at this time. This study aims to determine the effect of the promotion mix which consists of advertising, personal selling, sales promotion, publicity, direct marketing, and internet marketing to Decision of Car Oil Brand Selection at Pantai Gading Motor Palangkaraya. This study applies quantitative approach with explanatory research type and 115 people who are the consumers of Pantai Gading Motor Palangkaraya are chosen as respondents by using accidental sampling method. Data collection has been done by using questionnaires, the data has been analyzed by using multiple regression analysis, the F test is used to test the effect of simultaneous and t test is used to test the effect of partial at the 0.05 level.The results of this study proves that the promotion mix which consists of advertising, personal selling, sales promotion, publicity, direct marketing, and internet marketing simultaneously has positive and significant effect on decision of car oil brand selection at Pantai Gading Motor Palangkaraya. Partially, the variable of advertising, personal selling, sales promotion and internet marketing have a significant effect towards the decision of car oil brand selection at Pantai Gading Motor Palangkaraya while publicity variable and direct marketing give no significant effect decision of car oil brand selection at Pantai Gading Motor Palangkaraya.Keywords: Promotion Mix, Advertising, Personal Selling, Sales Promotion, Publicity, Direct Marketing, Internet Marketing, Decision of Brand Selection.